p55 and p75 tumor necrosis factor receptors are expressed and mediate common functions in synovial fibroblasts and other fibroblasts. - Butler, D; Feldmann, M; Di Padova, F; Brennan, F (1994)
There is increasing evidence that TNF-alpha is a cytokine of major importance in the pathogenesis of rheumatoid arthritis. Since TNF-alpha mediates its effects via high affinity receptors, we were interested in investigating their expression and function in cells from rheumatoid tissue. Synovial fibroblasts derived from rheumatoid synovial tissue are stimulated by TNF-alpha to proliferate and release cytokines, prostaglandins, proteases and protease inhibitors. We have evaluated through which receptor stimulation of DNA synthesis and the release of the proinflammatory agents, IL-6, IL-8 and PGE2 are induced. It was found that rheumatoid synovial fibroblasts express both the p55 and p75 TNF receptor, in a ratio of 4:1. TNF-alpha-stimulated synovial fibroblast DNA synthesis and the release of IL-6, IL-8 and PGE2 was inhibited by antagonist monoclonal antibodies against either the p55 or the p75 TNF receptor, although the blockade of the p55 TNF receptor had a more potent effect than inhibition of the p75 TNF receptor alone. Similarly, specific monoclonal antibodies, agonistic for either the p55 or p75 TNF receptor stimulated synovial fibroblast DNA synthesis, as well as IL-6, IL-8 and PGE2 release. Both p55 and p75 TNF receptors on dermal and gingival fibroblasts were also involved in TNF-alpha-mediated DNA synthesis and IL-6, IL-8 and PGE2 release, although differences in the levels of DNA synthesis and release of inflammatory cytokines and PGE2 were observed between the three fibroblast types.